Population genetic analyses provide insights on the introduction pathway and spread patterns of the North American forest pathogen Heterobasidion irregulare in Italy. Issue 19 (29th August 2013) - Garbelotto, M.; Guglielmo, F.; Mascheretti, S.; Croucher, P. J. P.; Gonthier, P.
Abstract: A population genetics approach is used to identify the most likely introduction site and introduction pathway for the North American forest pathogen Heterobasidion irregulare using 101 isolates from six sites in Italy and 34 isolates from five sites in North America. Diversity indices based on sequences from ten loci indicate the highest diversity in Italy is found in Castelfusano/Castelporziano and that diversity progressively decreases with increasing distance from that site. AMOVA, Bayesian clustering and principal coordinates analyses based on 12 SSR loci indicate high levels of gene flow among sites, high frequency of admixing, and fail to identify groups of genotypes exclusive to single locations. Cumulatively, these analyses suggest the current infestation is the result of multiple genotypes expanding their range from a single site. Based on two sequenced loci, a single source site in North America could provide enough variability to explain the variability observed in Italy. These results support the notion that H. irregulare was introduced originally in Castelporziano: because Castelporziano has been sealed off from the rest of the world for centuries except for a camp set up by the US military in 1944, we conclude the fungus may have been transported in infected wood used by the military. Finally, spatial autocorrelation analyses using SSR data indicate a significant under‐dispersion of alleles up to 0.5–10 km, while a significant overdispersion of alleles was detected at distances over 80 km: these ranges can be used to make predictions on the likely dispersal potential of the invasive pathogen.